Pre-Marital Counseling Effectiveness In Building Happy Muslim Families - Mohammad Nasir; Zainal Abidin; Lukman S. Thahir (State Institute for Islamic Studies Palu, 2021)
This study discusses the effectiveness of premarital guidance and counseling in building sakinah families at the Office of Religious Affairs (KUA) of Parigi District, Parigi Moutong Regency. The study used qualitative methods and the data was gathered through observation, indepth interviews and written material. The data analysis was analyzed through reduction process, then the data was presented in a table, and it was also verified, and finally the discussion was built based on the data. The results showed that (1) Guidance and premarital counseling in KUA Parigi District has been effectively carried out through premarital counseling and counseling programs carried out through two stages namely the pre-implementation stage and the implementation stage by increasing the role of the counselor in handling divorce, and guidance and pre-marital counseling with procedures that have been determined based on the existing schedule and comprehensive pre-marital guidance materials guided by KUA Employees and several other relevant agencies.